A Comparative Study of Chemical Routes for Coating Gold Nanoparticles via Controlled RAFT Emulsion Polymerization. (7th November 2016) - Pereira, Sónia O.; Barros‐Timmons, Ana; Trindade, Tito
Abstract : The synthesis of core‐shell Au nanoparticles protected by an amphiphilic block copolymer is investigated by distinct reversible addition fragmentation chain transfer (RAFT) emulsion polymerization routes. The controlled polymerization of polymer shells onto Au nanoparticles is attempted by using the macroRAFT (MR) agent based on 2‐(dodecylthiocarbonothioylthio)‐2‐methylpropionic acid synthesized via RAFT polymerization of poly(ethylene glycol) methyl ether acrylate and exploring several approaches, which include (i) post‐modification; (ii) in situ synthesis and (iii) "grafting from" strategies. In the conditions investigated here all these strategies lead to Au polymer nanocomposites but morphological well‐defined core‐shell nanoparticles are only obtained by applying the "grafting from" strategy. In particular, conditions that promote chain extension from the MR agent adsorbed onto the Au nanoparticles are found necessary to obtain nanostructures with such morphological characteristics and that still show the localized surface plasmon resonance typical of colloidal Au nanoparticles. Abstract : Colloidal core‐shell Au nanoparticles protected by amphiphilic block copolymer have been investigated by applying distinct reversible addition fragmentation chain transfer emulsion polymerization routes, but only the "grafting from" strategy provides morphological well‐defined hybrid nanoparticles.